2018
DOI: 10.1371/journal.pone.0203344
|View full text |Cite
|
Sign up to set email alerts
|

Inequality in total fertility rates and the proximate determinants of fertility in 21 sub-Saharan African countries

Abstract: In this paper, we examine the inequality in the dynamics of the total fertility rate within 21 sub-Saharan African countries by wealth quintiles. We also examine the associated inequality within each country in the proximate determinants of fertility–marriage, contraception, and breastfeeding. Applying Bongaarts’ proximate determinants of fertility framework, for 14/21 countries we analyze, we find that those in the richest wealth quintiles have had a more rapid decline in fertility rates than those in the poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 23 publications
(26 reference statements)
6
27
0
Order By: Relevance
“…This current research is similar to a previous study conducted in 21 sub-Saharan African countries based on the economic status of women. 12 Another interesting outcome of the research showed that women who experience an abortion during their reproductive years have a higher fertility rate than women who do not. This is contrary to the results of various previous studies conducted in Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This current research is similar to a previous study conducted in 21 sub-Saharan African countries based on the economic status of women. 12 Another interesting outcome of the research showed that women who experience an abortion during their reproductive years have a higher fertility rate than women who do not. This is contrary to the results of various previous studies conducted in Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
“…10 The decline in fertility in sub-Saharan Africa is related to numerous women remaining unmarried and, to a lesser degree, increased contraceptive use. 11 In a study of 21 sub-Saharan African countries, the researcher 12 determined that women from rich households have a swifter reduction in fertility rates, greater delay in marrying, and higher contraceptive use compared with women from poor households.…”
mentioning
confidence: 99%
“…For other authors, there is an inverse J-shaped between poverty and fertility (Aassve and Woldegebrie, 2006). According to Easterlin (1969Easterlin ( , 1973aEasterlin ( , 1980, if the standard living of household is not better than what people knew during their adolescence, fertility can probably decline. The negative relationship is attributed to a number of reasons: (i) high fertility is considered a rational response to poverty (Becker and Lewis, 1973), so that, the benefits of having children outweigh their costs, leading to high demand for children, hence high fertility (Odwe, 2015); (ii) high infant mortality rate which tends to be stronger in poor households (Lutz, 1987).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Nigeria, increased use of contraception and changes in marriage pattern were found to be associated with the fertility decline [17]. Another study concluded that the richest in Nigeria compared to the poorest were depending more on delayed marriage and contraception for fertility reduction [29,30]. Also fertility has been estimated at both national and across the six geopolitical zones in Nigeria by previous studies [12,13,14,15,16,44].…”
Section: Introductionmentioning
confidence: 99%